Tissue expanders with a focus on extremity reconstruction. (1st February 2018) - Arain, Abdul R.; Cole, Keegan; Sullivan, Christopher; Banerjee, Samik; Kazley, Jillian; Uhl, Richard L.
ABSTRACT: Introduction : Acute traumatic or surgical wounds that cannot be primarily closed often cause substantial morbidity and mortality. This often leads to increased costs from higher material expenses, more involved nursing care, and longer hospital stays. Advancements in soft tissue expansion has made it a popular alternative to facilitate early closure without the need for more complicated plastic surgical procedures. Areas covered : In this review, we briefly elaborate on the history and biomechanics of tissue expansion and provide comprehensive descriptions of traditional internal tissue expanders and a variety of contemporary external tissue expanders. We describe their uses, advantages, disadvantages, and clinical outcomes. The majority of articles reviewed include case series with level IV evidence. Outcome data was collected for studies after 1990 using PubMed database. Expert commentary : An overall reduction in cost, time-to-wound closure, hospital length-of-stay, and infection rate may be expected with most tissue expanders. However, further studies comparing outcomes and cost-effectiveness of various expanders may be beneficial. Surgeons should be aware of the wide array of tissue expanders that are commercially available to individualize treatment based on thorough understanding of their advantages and disadvantages to optimize outcomes. We predict the use of external expanders to increase in the future and the need for more invasive procedures such as flaps to decrease.